Influence of dietary fat source and feeding duration on pig growth performance, carcass composition, and fat quality - Stephenson, Ethan W.; Vaughn, Mathew A.; Burnett, Derris D.; Paulk, Chad B.; Tokach, Michael D.; Dritz, Steven S.; DeRouchey, Joel M.; Goodband, Robert D.; Woodworth, Jason C.; Gonzalez, John M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 160 finishing pigs (PIC 327 × 1050; initially 100.5 lb) were used in an 84-d experiment to evaluate the effects of dietary fat source and feeding duration on growth performance, carcass characteristics, and fat quality. Dietary treatments included a corn-soybean meal control diet with no added fat or a 3 × 3 factorial with main effects of fat source (4% tallow, 4% soybean oil, or a blend of 2% tallow and 2% soybean oil) and feeding duration (d 0 to 42, 42 to 84, or 0 to 84). One pig was identified in each pen on d 0, and biopsy samples of the back, belly, and jowl fat were collected on d 0, 41, and 81. At the conclusion of the study, all pigs were harvested, carcass characteristics were measured, and back, belly, and jowl fat samples were collected. Overall (d 0 to 84), there were no differences between fat sources for growth and carcass characteristics; however, pigs fed diets with added fat from d 0 to 84 had improved (P < 0.036) F/G compared with pigs fed a control diet without added fat. Pigs fed added fat throughout the entire study also had improved (P < 0.042) ADG and F/G and heavier d-84 BW (P < 0.006) compared with pigs fed additional fat for only period 1 or 2. Adding fat for the entire study increased (P < 0.032) backfat and tended to reduce (P < 0.083) fat-free lean index compared with pigs fed the control diet without added fat. Added fat also increased (P < 0.05) iodine value (IV) compared with pigs fed the control diet. Increasing the feeding duration of soybean oil or a blend of soybean oil and tallow decreased monounsaturated and increased polyunsaturated fatty acids relative to feeding tallow (duration × fat source interaction, P < 0.05), with the greatest changes in C18:1 and C18:2, respectively. In conclusion, feeding added fat improved ADG and F/G; however, feeding soybean oil for increasing duration, either alone or in a blend with tallow, negatively affected the fatty acid composition and IV of finishing pigs.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: fin; Iodine value; Fat; Feeding duration